The material of the social: the mutual shaping of institutions by irrigation technology and society in Seguia Khrichfa, Morocco. Issue 1 (March 2015) - van der Kooij, Saskia; Zwarteveen, Margreet; Kuper, Marcel
In this paper we draw attention to the important role technology plays in co-mediating institutions, opening up some courses of action and closing off others. Irrigation studies generally recognize the importance of institutions in making technologies work, but tend to take the precise functioning of institutions for granted. Studies that analyse institutions often do not pay enough attention to the mediating role of technology in allocating benefits, risks and burdens. We show in this paper that (irrigation) institutions are moulded by and come about through the interactions between the technical and the social in dynamic and often contested processes of adaptation to changing environments. We argue that a critical understanding of what institutions do requires more explicit and detailed attention to technologies. We base this argument on a detailed historical analysis of the functioning of Seguia Khrichfa, a farmer managed irrigation scheme in Morocco. Through time, irrigation institutions in the Seguia Khrichfa have undergone transformations to match the changing demands of a heterogeneous and growing group of irrigators, an increased command area and changing cropping patterns, and the introduction of new technologies such as drip irrigation. These institutional transformations consisted of recursive cycles of modifications in technological infrastructure and the rules of allocation and distribution. Technical adaptations prompt alterations in the water rotation schedule and vice versa. We anchor our case in descriptions of a specific technology that played a crucial role in co-steering institutional change: the introduction of open/closed gates. Our analysis of the co-evolution of society and technology in shaping institutions in the Seguia Khrichfa shows how technologies become enrolled in (sometimes implicit) processes of re-negotiating relations of authority and responsibility while obscuring institutional politics.